Differential protein expressions associated with dental implant healing - Abd Wahab, Muhammad Amal; Mohd Yusof, Eleena; James, Richard Muhammad Johari; Noorhizab, Mohd Nur Fakhruzzaman; Kek, Teh Lay; Salleh, Mohd Zaki; Ahmad, Rohana (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
Purpose of the research- Dental implants' topographical features are critical in regulating the healing process and, consequently, the production of proteins involved in multiple stages, from the initial inflammatory response to the following remodelling of the bone. Improved bone-to-implant contact and favourable cellular responses have been shown when a rough implant surface is present. But to get the appropriate level of roughness, additional procedures are usually required, which raises the total cost of dental implants. Using metal injection moulding technology, a porous dental implant composed of nickel titanium (NiTi) has been produced successfully. This novel method makes it unnecessary to make additional surface alterations, making it a more economical alternative. However, further research needs to be done to determine which protein expressions are associated with the faster healing of porous implants, as shown by an earlier study in an animal model. The objective of this investigation was to identify and compare the proteins that are produced during the healing process in dental implants, both with and without porous properties. Methods- The study comprised a total of fourteen participants, with seven participants receiving the NiTi dental implant and seven participants receiving the Mega Gen dental implant (control group). Saliva samples were obtained at three distinct time intervals: prior to implantation (T0), one-week post-implantation (T1), and eighteen weeks’ post-implantation (T2). The proteins involved in bone regeneration were analyzed in saliva using liquid chromatography-mass spectrometry (LC-MS, Model 6520- Accurate Mass Q-TOF). Results- Gene ontology analysis revealed 15 proteins associated with osseointegration in the MegaGen group, detected at various time points (T0, T1, and T2). These proteins included Pancreatic alpha- amylase (T0, T1, T2), Fibronectin (T0), Putative POU domain, class 5, transcription factor 1B (T0), Titin (T0, T2), Cellular tumor antigen p53 (T1, T2), Neuroserpin (T1), Collagen alpha-3(VI) chain (T1), Dystonin (T1), Ubiquitin carboxyl-terminal hydrolase 19 (T1), basement membrane-specific heparan sulfate proteoglycan core protein (T2), EH domain-containing protein 1 (T2), myosin-11 (T2), TLR4 interactor with leucine-rich repeats (T2), Talin-1 (T2), and Thrombospondin-1 (T2). In the NiTi group, 7 proteins were identified, including Fibronectin at T0 and T2, Pancreatic alpha-amylase at T0, T1, and T2, Titin and Hepatocyte growth factor at T0, T1, and T2, Zinc finger and BTB domain-containing protein 40 at T1, Endothelin-1 at T2, and Fibrillin-2 at T2. Conclusion- The proteins associated with the MegaGen group offer a detailed elucidation of the osseointegration process, particularly during the phases of cell proliferation and bone remodelling. The proteins associated with the NiTi group may have a link not only to osseointegration but also to inflammation.